AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT WRITTEN BY STUDENTS OF THE TENTH GRADE AT SMA N 1 GODONG - Mei Purnama Sari; Suwandi Suwandi; Dias Andris Susanto (Wawasan Pendidikan, 2023)
This final project studied the analysis of the errors made by the students. The background of the study errors made the students. This research focused mainly on the errors finding. The design of the research was descriptive qualitative research. The objectives of the study were (1) to find out the kinds of errors finding, (2) to explore dominant errors findings, (3) to show the students competence producing descriptive text. The object of the research were tenth grade SMA N 1 Gondong. The instruments of the study were the data from the students product. To identify the data of error analysis the researcher used the theory of James Carl (1998). This finding showed us how the errors finding. The dominant types of errors analysis is the omission 42 findings with 42,42% percentage finding from the data. Then, followed by the misinformation that found 32 errors with 32,32%. The 15 errors of addition with the percentage 15,15% findings from the data. The last one is misordering with 10 errors with 10,10%. The summaries may be concluded that there were several finding on the errors analysis. There were omission, addition, misinformation, and misordering.